Unmanned Aerial Vehicle (UAV)-Based for Slope Mapping and the Determination of Potential Slope Hazard - Zolkepli, M. F.; Ishak, M. F.; Abu Talib, Z. (International Journal of Integrated Engineering, 2022)
This paper discusses the applications of unmanned aerial vehicle (UAV) for geological mapping and the determination of cross-section of certain selected area. With the development of modern technology, the utilization of UAV to gather data for geological mapping can be considered as finest method as it is quick, reliable, precise, cost-effective and also easily to operate. High imagery quality is essential for the effectiveness and nature of normal mapping output such as Digital Surface Model (DSM) and also Ortho Images. The utilization of UAV to capture aerial photo helps to gather information from a normal area to an area which almost impossible to reach. With the data obtained by the UAV, it will later be processed in established software and the analysis of slope profile of certain selected study area will be done. From these analyses, the potential slope hazards which based on slope angles will be determined and considered as another interest of this study.